Problem solving courts: social science and legal perspectives (Springer, 2013)
Social psychology and problem-solving courts: judicial roles and decision making / Richard L. Wiener and Leah Georges -- The marriage of science and the law in child welfare cases / Cindy S. Lederman -- Exploring the value-added of specialized problem-solving courts for dependency cases / Sophia I. Gatowski, Shirley A. Dobbin and Alicia Summers -- Dependency courts and science / Victoria Weisz -- Unified family courts: an interdisciplinary framework and a problem-solving approach / Barbara A. Babb -- Domestic violence courts: the case of lady justice meets the serpents of the caduceus / Nancy Wolff -- Gender issues in problem-solving courts / Anna Williams Shavers -- Mental health courts may work, but does it matter if they do? / John Petrila -- The past, present, and future of mental health courts / Allison D. Redlich -- Mental health courts: competence, responsibility, and proportionality / Robert F. Schopp -- The evolution of problem-solving courts in Australia and New Zealand: a trans-Tasman comparative perspective / Elizabeth Richardson, Katey Thom and Brian McKenna -- Problem solving courts: therapeutic jurisprudence in practice / Bruce J. Winick -- The intended and unintended consequences of problem-solving courts / Eve M. Brank and Joshua A. Haby